EFEKTIVITAS BUAH KURMA (PHOENIX DACTYLIFERA) DENGAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER 2 - Ferilia Adiesti; Nurun Ayati Khasanah; Citra Adityarini Safitri (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Anemia is the main cause of maternal death. Pregnant women who suffer from anemia will experience postpartum bleeding, as a result of this bleeding the mother will experience prolonged health problems and even result in death The purpose of this study was to determine the effectiveness of giving dates to increase Hb levels in pregnant women. This research design uses a Pre-experimental design research method (One-Group Pretest-Posttest Design), namely by means of a nonrandomized control group pretest-posttest design comparing two groups, namely the experimental class and the control class. The sample in this study were all pregnant women who experienced anemia as many as 30 respondents. The results of the analysis showed that the average hemoglobin level of anemic pregnant women who were given blood-boosting tablets was 10.4 gr/dl. Hemoglobin levels of anemic pregnant women before being given dates averaged 9.0 gr/dl and after being given dates averaged 10.0 gr/dl and above. In raising Hb levels in pregnant women who experience anemia, date fruit is more effectively consumed with Fe tablets compared to consuming Fe tablets alone with a value of p = 0.045 (p <0.05) that there is an effectiveness of giving date fruit with an increase in Hb levels in pregnant women in PMB “F” in 2022 with a value of p = 0.045 (p <0.05). From the study it was found that date juice increased HB levels in second trimester pregnant women with an average increase per week of 0.2-1.4 per week.